Transformations of the architecture symbolic language in the modern city space: the dialogue and confrontation collisions - S. P. Stoian (Ukrainian Cultural Studies, 2019)
The article analyzes the transformation of the architecture symbolic language in modern cities, which is associated with the practice of actively updating the urban space through the implementation of innovative and sometimes extremely radical architectural projects. An attempt is being made, from standpoint of the time distance to assess the change in views on extremely controversial structures, the construction of which at one time caused great scandals and devastating criticism, but with the change of cultural priorities and values, they became houses of worship and symbols of famous European cities.Over the last century, each and all of the fields of culture have undergone significant changes, including the visual sphere, with such an important component as architecture, which for thousands of years has transmitted non-verbal information about the cultural specificity of the past through thousands of visual symbolic codes. As for now, the viability and allowability issue of radical transformations of urban architectural space under the influence of new technologies and innovative trends is extremely acute. The traditions and innovations problem, the need to involve cultural experts in order to preserve the unique historical spaces of world-famous landmarks, requires a great deal of attention from cultural experts, who should carry out a thorough analysis of the problem and formulate practical advice for resolving debates on shaping the architectural space of modern cities.In an effort to distance itself from the extremely radical critical views of contemporary architectural innovations, the focus is on finding sound solutions to the dramatic transformations of historic centers of contemporary cities that must be made with cultural experts and professionals of the relevant field involvement.
Keywords: symbolism, architecture, city, construction, traditions, innovations